2021
DOI: 10.1108/ijmpb-12-2020-0381
|View full text |Cite
|
Sign up to set email alerts
|

Four images of projectification: an integrative review

Abstract: PurposeThe aim of this article is to give an overview of the development and current state of projectification research. The inquiry was driven by a threefold research question: How has projectification been understood and defined over time, what has the trajectory of the development been and what are the main trends and emerging ideas?Design/methodology/approachThe article is an integrative literature review of research done on the notion of projectification to date. An interdisciplinary, integrative literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 68 publications
0
22
0
1
Order By: Relevance
“…There were no significant differences in the other scales (Table 1). In the control group, there was a significant difference between the measurement points for the scale worries (X 2 (2, n = 6) = 7.11, p = 0.022) and tension (X 2 (2, n = 6) = 8.27, p = 0.016). Posthoc-tests revealed that this difference lost significance (z = 1.133, p corrected = 0.063).…”
Section: Development Of Participants' Skillsmentioning
confidence: 92%
See 1 more Smart Citation
“…There were no significant differences in the other scales (Table 1). In the control group, there was a significant difference between the measurement points for the scale worries (X 2 (2, n = 6) = 7.11, p = 0.022) and tension (X 2 (2, n = 6) = 8.27, p = 0.016). Posthoc-tests revealed that this difference lost significance (z = 1.133, p corrected = 0.063).…”
Section: Development Of Participants' Skillsmentioning
confidence: 92%
“…As a reaction to growing complexity and environmental dynamics, organizations resort to projectification as a managerial approach [1,2]. In Germany, like other Western economies, 34.7% of work is organized in the form of projects [3].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it expands the methodological repertoire for studying the agility phenomenon by synthetizing insights gained from a set of case studies centered around the scaling of agile practices. Additionally, this study also makes a valuable contribution to the discourse on “deprojectification,” that is currently emerging within the project management discipline (Jacobsson and Jałocha, 2021; Nesheim, 2023). From a managerial perspective, this study illuminates the challenges that arise within large organizations when attempting to scale agile practices.…”
Section: Introductionmentioning
confidence: 92%
“…On the one hand, projectification of society can be understood as process or development towards an increasing importance of projects in broad areas of society (Munck af Rosenschöld, 2019). On the other hand, it “indicates an interest in the outcomes and consequences of projectification on parts of the society or on society at large” (Jacobsson and Jalocha, 2021, p. 1593). It has become generally accepted that projectification extends beyond single organizations' boundaries.…”
Section: Theoretical Grounding Of the Studymentioning
confidence: 99%